Ni-Cr-Mo precipitation hardening alloy
The Ni-Cr-Mo alloy addresses the limitations of existing alloys by enhancing corrosion and wear resistance through precise composition and microstructure, enabling effective plastic working.
Patent Information
- Application Number
- JP2023148651
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-02
- Filing Date
- 2023-09-13
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2039-09-10
AI Technical Summary
Existing Ni-based alloys face challenges in forming solid solutions for plastic working due to difficulty in boride formation, and insufficient corrosion resistance due to inadequate elements in the matrix.
A Ni-Cr-Mo precipitation hardening alloy with specific compositions and microstructural features, including grain boundaries, a matrix with dispersed γ' phase, and Mo compound phases, enhances corrosion resistance, wear resistance, and machinability.
The alloy achieves excellent corrosion resistance, wear resistance, and machinability through controlled alloying and heat treatment processes, resulting in improved mechanical properties.
Smart Images

Figure 0007602594000003 
Figure 0007602594000004 
Figure 0007602594000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a precipitation hardening alloy containing Ni, Cr and Mo. [Background technology]
[0002] Ni-based alloys, Co-based alloys, etc. are used in applications requiring corrosion resistance and wear resistance. Various improvements have been proposed for these alloys with the intention of using them in more severe environments.
[0003] Japanese Patent No. 3983644 proposes an alloy in which borides are dispersed in a matrix mainly composed of Ni. The borides are hard. The borides can contribute to the wear resistance of the alloy.
[0004] Japanese Patent No. 4816950 proposes a Ni-Cr-Mo alloy in which intermetallic compounds are dispersed in a matrix mainly composed of Ni. The intermetallic compounds can contribute to the wear resistance of the alloy. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 3983644 [Patent Document 2] Patent No. 4816950 Summary of the Invention [Problem to be solved by the invention]
[0006] In the alloy disclosed in Japanese Patent No. 3983644, the borides are difficult to redissolve, and therefore this alloy is not suitable for plastic working.
[0007] In the alloy disclosed in Japanese Patent No. 4816950, the amount of elements that can contribute to corrosion resistance in the matrix tends to be insufficient, and the corrosion resistance of this alloy is not sufficient.
[0008] An object of the present invention is to provide a Ni-Cr-Mo precipitation hardened alloy having excellent corrosion resistance, wear resistance and machinability. [Means for solving the problem]
[0009] The Ni-Cr-Mo precipitation hardening alloy according to the present invention has the following properties: Cr: 18.0 mass% or more and 28.0 mass% or less, Mo: 10.0% by mass or more and 25.0% by mass or less, and Al: 1.0 mass% or more and 3.0 mass% or less The balance is Ni and unavoidable impurities.
[0010] Preferably, the precipitation hardened alloy has a metal structure including grain boundaries, a matrix, and a γ' phase dispersed in the matrix. The matrix contains Ni, Cr, and Mo. The sum P1 of the ratio of Cr and the ratio of Mo in the matrix is 25% by mass or more and 50% by mass or less.
[0011] Preferably, this metal structure has a Mo compound phase dispersed in the grain boundaries and the matrix. The sum P2 of the ratio of Cr and the ratio of Mo in this Mo compound phase is 60 mass % or more and 80 mass % or less.
[0012] Preferably, the ratio R1 of the sum of the mass of Al in the matrix and the mass of Al in the γ' phase dispersed in the matrix to the total mass of Al is 0.6 or more. Preferably, the ratio R2 of the mass of Al in the Mo compound phase dispersed in the grain boundaries and the matrix to the total mass of Al is 0.4 or less.
[0013] According to another aspect, the Ni-Cr-Mo based precipitation hardening alloy of the present invention comprises: Cr: 18.0 mass% or more and 28.0 mass% or less, Mo: 10.0% by mass or more and 25.0% by mass or less, and Al: 1.0 mass% or more and 3.0 mass% or less The alloy further contains up to 2.0% by weight of Nb and / or up to 2.0% by weight of Ti, with the balance being Ni and unavoidable impurities.
[0014] Preferably, the precipitation hardened alloy has a metal structure including grain boundaries, a matrix, and a γ' phase dispersed in the matrix. The matrix contains Ni, Cr, and Mo. The sum P1 of the ratio of Cr and the ratio of Mo in the matrix is 25% by mass or more and 50% by mass or less.
[0015] Preferably, this metal structure has a Mo compound phase dispersed in the grain boundaries and the matrix. The sum P2 of the ratio of Cr and the ratio of Mo in this Mo compound phase is 60 mass % or more and 80 mass % or less.
[0016] Preferably, the ratio R1 of the sum of the mass of Al in the matrix and the mass of Al in the γ' phase dispersed in the matrix to the total mass of Al is 0.6 or more. Preferably, the ratio R2 of the mass of Al in the Mo compound phase dispersed in the grain boundaries and the matrix to the total mass of Al is 0.4 or less.
[0017] Preferably, the ratio R3 of the mass of Nb in the Mo compound phase dispersed in the grain boundaries and the matrix to the total mass of Nb is 0.6 or less.
[0018] Preferably, the ratio R4 of the mass of Ti in the Mo compound phase dispersed in the grain boundaries and the matrix to the total mass of Ti is 0.6 or less. Effect of the Invention
[0019] The Ni-Cr-Mo precipitation hardened alloy according to the present invention is excellent in corrosion resistance, wear resistance and machinability. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a photograph showing the results of electron beam diffraction of a material for a precipitation hardened alloy according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a photograph showing the results of electron beam diffraction of a precipitation hardened alloy according to one embodiment of the present invention. [Diagram 3] FIG. 3 is an SEM image showing a cross section of the precipitation hardened alloy of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Hereinafter, the present invention will be described in detail based on preferred embodiments.
[0022] The Ni-Cr-Mo precipitation hardening alloy according to the present invention has the following properties: Cr: 18.0 mass% or more and 28.0 mass% or less, Mo: 10.0 mass% or more and 25.0 mass% or less and Al: 1.0 mass% or more and 3.0 mass% or less The alloy further comprises Nb: 2.0% by mass or less and / or Ti: 2.0% by mass or less The balance is Ni and unavoidable impurities.
[0023] This alloy has grain boundaries, a matrix, and a number of compound phases dispersed in the matrix. The compound phases are precipitated through solution treatment, aging treatment, etc., and are dispersed in the matrix. The main component of this matrix is Ni. In this matrix, Cr or Mo is solid-solved in Ni. Typical compound phases are γ' phase and Mo compound phase. The γ' phase can precipitate regardless of the presence or absence of Nb and Ti in the alloy. The Mo compound phase can precipitate when the alloy contains Nb or Ti. The Mo compound phase can be dispersed not only in the matrix but also in the grain boundaries. This alloy does not substantially contain B. This alloy has excellent machinability. In the present invention, machinability means the ease of plastic processing performed at a stage before heat treatment such as aging treatment is performed.
[0024] [Molybdenum (Mo)] Mo dissolves in the base material Ni and contributes to the corrosion resistance of the alloy. Mo especially contributes to the corrosion resistance against non-oxidizing acids. When a base material containing Mo is subjected to solution treatment and aging treatment, a large number of Mo compound phases are precipitated. These Mo compound phases are dispersed in the matrix. The main component of the Mo compound phase is Mo. This Mo compound phase has high hardness. This Mo compound phase can contribute to the wear resistance of the alloy.
[0025] From the viewpoint of precipitating a sufficient Mo compound phase and allowing sufficient Mo to exist in the matrix after the precipitation of the Mo compound phase, the Mo content is preferably 10.0 mass% or more, more preferably 12.0 mass% or more, and particularly preferably 14.0 mass% or more. From the viewpoint of the cost of the alloy, the Mo content is preferably 25.0 mass% or less, more preferably 23.0 mass% or less, and particularly preferably 21.0 mass% or less.
[0026] Chromium Cr dissolves in the base material Ni and contributes to the corrosion resistance of the alloy. Cr especially contributes to the corrosion resistance against various acids. Cr can be contained in the Mo compound phase precipitated by solution treatment and aging treatment. This Mo compound phase has high hardness. This Mo compound phase can contribute to the wear resistance of the alloy.
[0027] From the viewpoint that a Mo compound phase having sufficient Cr is precipitated and sufficient Cr can be present in the matrix after precipitation of the Mo compound phase, the Cr content is preferably 18.0 mass% or more, more preferably 20.0 mass% or more, and particularly preferably 21.0 mass% or more. From the viewpoint of the cost of the alloy, the Cr content is preferably 28.0 mass% or less, more preferably 26.0 mass% or less, and particularly preferably 24.0 mass% or less.
[0028] [Aluminum (Al)] Al dissolves in the Ni base material. When a base material containing Al is subjected to solution treatment and aging treatment, a large number of γ' phases (Ni3Al phases) precipitate. These γ' phases are dispersed in the matrix. An alloy containing this γ' phase has high hardness. This γ' phase contributes to the wear resistance of the alloy.
[0029] From the viewpoint of sufficient precipitation of the γ' phase, the Al content is preferably 1.0 mass% or more, more preferably 1.5 mass% or more, and particularly preferably 2.0 mass% or more. This content is preferably 3.0 mass% or less.
[0030] [Niobium (Nb)] Nb dissolves in the base material Ni. The amount of Nb dissolved in Ni during solution treatment is greater than that of Al. In alloys containing Nb, many Mo compounds can dissolve in solution treatment. This alloy has a large difference in hardness before and after aging treatment. This alloy has high machinability after solution treatment. Nb further dissolves in the γ' phase by substitution with Al to form the Ni3(Al,Nb) phase. This γ' phase hardens by aging treatment. Nb can contribute to the wear resistance of the alloy.
[0031] From the viewpoint of sufficient precipitation of the γ' phase, the Nb content is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and particularly preferably 0.5 mass% or more. This content is preferably 2.0 mass% or less.
[0032] Nb is not an essential element. Therefore, the content of Nb may be substantially zero. In an alloy that does not contain Nb or Ti, Mo compounds do not precipitate. This alloy has excellent corrosion resistance. In this alloy, the γ' phase contributes to wear resistance.
[0033] [Titanium (Ti)] Ti dissolves in the base material Ni. The amount of Ti dissolved in Ni during solution treatment is greater than that of Al. In alloys containing Ti, many Mo compounds can dissolve in solution treatment. This alloy has a large difference in hardness before and after aging treatment. This alloy has high machinability after solution treatment. Ti further dissolves in the γ' phase through substitution with Al to form the Ni3(Al,Ti) phase. This γ' phase hardens through aging treatment. Ti can contribute to the wear resistance of the alloy.
[0034] From the viewpoint of sufficient precipitation of the γ' phase, the Ti content is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and particularly preferably 0.5 mass% or more. This content is preferably 2.0 mass% or less.
[0035] Ti is not an essential element, and therefore the Ti content may be substantially zero.
[0036] [Nb and Ti] The alloy may contain both Nb and Ti. In this case, Nb dissolves in the γ' phase by substitution with Al, and T dissolves in the γ' phase by substitution with Al to form the Ni3(Al,Nb,Ti) phase. This γ' phase is hardened by aging treatment. The alloy containing both Nb and Ti has excellent wear resistance.
[0037] [Cr and Mo in the matrix] The total P1 of the ratio of Cr and the ratio of Mo in the matrix is preferably 25% by mass or more and 50% by mass or less. An alloy having a total ratio P1 of 25% by mass or more has excellent corrosion resistance. From the viewpoint of corrosion resistance, this ratio P1 is more preferably 28% by mass or more, and particularly preferably 31% by mass or more. An alloy having a ratio P1 of 50% by mass or less has excellent toughness. Therefore, the flexural strength of this alloy is large. From the viewpoint of flexural strength, this ratio P1 is more preferably 48% by mass or less, and particularly preferably 45% by mass or less. The ratio of Cr in the matrix is the percentage of the mass of Cr contained in the matrix with respect to the total mass of the matrix. The ratio of Mo in the matrix is the percentage of the mass of Mo contained in the matrix with respect to the total mass of the matrix.
[0038] [Cr and Mo in Mo compound phase] The total P2 of the ratio of Cr and the ratio of Mo in the Mo compound phase dispersed in the grain boundary and the matrix is preferably 60% by mass or more and 80% by mass or less. The Mo compound phase having a total ratio P2 of 60% by mass or more has high strength. The alloy having this Mo compound phase has a large flexural strength. From the viewpoint of flexural strength, this ratio P2 is more preferably 63% by mass or more, and particularly preferably 65% by mass or more. In an alloy having this ratio P2 of 80% by mass or less, sufficient Cr and Mo are solid-dissolved in Ni in the matrix. This alloy has excellent corrosion resistance. From the viewpoint of corrosion resistance, this ratio P2 is more preferably 77% by mass or less, and particularly preferably 75% by mass or less. The ratio of Cr in the Mo compound phase is the percentage of the mass of Cr contained in the Mo compound phase with respect to the total mass of the Mo compound phase. The ratio of Mo in the Mo compound phase is the percentage of the mass of Mo contained in the Mo compound phase with respect to the total mass of the Mo compound phase.
[0039] [Al in matrix and γ' phase] The ratio R1 of the sum W1 of the mass of Al in the matrix and the mass of Al in the γ' phase dispersed in the matrix to the total mass TA of Al is preferably 0.6 or more. An alloy in which this ratio R1 is 0.6 or more contains a sufficient amount of γ' phase. This alloy has excellent wear resistance. From the viewpoint of wear resistance, this ratio R1 is more preferably 0.7 or more, and particularly preferably 0.8 or more. This ratio R1 may be 1.0. The amount of Al present in the grain boundaries is not included in the sum W1. The total mass TA of Al is the amount of all Al contained in this alloy.
[0040] [Al in Mo compound phase] The ratio R2 of the mass W2 of Al in the Mo compound phase dispersed in the grain boundaries and matrix to the total mass TA of Al is preferably 0.4 or less. In an alloy in which this ratio R2 is 0.4 or less, a sufficient amount of Al remains in the matrix or γ' phase. This alloy has a sufficient amount of γ' phase. This alloy has excellent wear resistance. From the viewpoint of wear resistance, this ratio R2 is more preferably 0.3 or less, and particularly preferably 0.2 or less. This ratio R2 may be 0.0. The mass W2 is the sum of the amount W2b of Al in the Mo compound dispersed in the grain boundaries and the amount W2m of Al in the Mo compound dispersed in the matrix. The total mass TA of Al is the amount of all Al contained in this alloy.
[0041] [Nb in Mo compound phase] The ratio R3 of the mass W3 of Nb in the Mo compound phase dispersed in the grain boundaries and matrix to the total mass TN of Nb is preferably 0.6 or less. In an alloy in which the ratio R3 is 0.6 or less, a sufficient amount of Nb remains in the matrix or γ' phase. This alloy has a sufficient amount of γ' phase. This alloy has excellent wear resistance. From the viewpoint of wear resistance, this ratio R3 is more preferably 0.5 or less, and particularly preferably 0.4 or less. This ratio R3 may be 0.0. The mass W3 is the sum of the amount W3b of Nb in the Mo compound dispersed in the grain boundaries and the amount W3m of Nb in the Mo compound dispersed in the matrix. The total mass TN of Nb is the amount of all Nb contained in this alloy.
[0042] When the alloy contains Ti together with Nb, the above-mentioned effect of Nb can also be exerted.
[0043] [Ti in Mo compound phase] The ratio R4 of the mass W4 of Ti in the Mo compound phase dispersed in the grain boundaries and matrix to the total mass TT of Ti is preferably 0.6 or less. In an alloy in which the ratio R4 is 0.6 or less, a sufficient amount of Ti remains in the matrix or γ' phase. This alloy has a sufficient amount of γ' phase. This alloy has excellent wear resistance. From the viewpoint of wear resistance, this ratio R4 is more preferably 0.5 or less, and particularly preferably 0.4 or less. This ratio R4 may be 0.0. The mass W4 is the sum of the amount W4b of Ti in the Mo compound dispersed in the grain boundaries and the amount W4m of Ti in the Mo compound dispersed in the matrix. The total mass TT of Ti is the amount of all Ti contained in this alloy.
[0044] When the alloy contains Nb together with Ti, the above-mentioned effect of Ti can also be exerted.
[0045] An example of a manufacturing method for the precipitation hardened alloy according to the present invention will be described below. In this manufacturing method, first, a material with adjusted composition is prepared. Next, this material is subjected to solution treatment. In the solution treatment, the material is held in an environment of 1000°C to 1250°C for 1 to 6 hours. The material is then cooled. Typical cooling methods include water cooling and air cooling. The solution treatment generates grain boundaries and a matrix. Compounds (e.g., Mo compounds) precipitate at the grain boundaries.
[0046] The results of electron beam diffraction of the material after the solution treatment are shown in Figure 1. All the light spots visible in Figure 1 are diffractions of γNi. As is clear from Figure 1, there is no γ' phase in this material. This material is subjected to mechanical plastic processing.
[0047] The material is then subjected to aging treatment. In aging treatment, the material is kept in an environment of 600°C to 800°C for 2 to 40 hours. The material is then cooled. Typically, the cooling is furnace cooling or air cooling. This aging treatment results in a precipitation hardened alloy.
[0048] The electron diffraction results of the precipitation hardened alloy immediately after aging are shown in Figure 2. The bright spots in Figure 2 are the diffraction of γNi. The faint spots between the adjacent bright spots are the diffraction of the γ' phase.
[0049] Figure 3 is an SEM image showing the cross section of this precipitation hardened alloy. Figure 3 shows the matrix and the dispersion. The main component of the matrix is Ni. The dispersion is a Mo compound phase.
[0050] The material after the solution treatment has a hardness of, for example, 240HV. This material has excellent machinability. On the other hand, the precipitation hardened alloy after the aging treatment has a hardness of, for example, 450HV. This precipitation hardened alloy has excellent wear resistance.
[0051] The material may be obtained by melting or by powder metallurgy. In the case of powder metallurgy, the powder may be obtained by atomization. A preferred atomization method is gas atomization. In gas atomization, the raw material is placed in a container (quartz crucible) with a small hole at the bottom. The raw material is heated and melted by a high-frequency induction furnace in an atmosphere of argon gas or nitrogen gas. Argon gas or nitrogen gas is sprayed onto the raw material flowing out from the small hole. The raw material is quenched and solidified, and a powder is obtained.
[0052] This powder is classified as necessary. The classified powder is filled into a capsule made of carbon steel. The inside of this capsule is evacuated and then sealed to obtain a billet. This billet is subjected to HIP (hot isostatic pressing). The preferred pressure for HIP is 50 MPa or more and 300 MPa or less, and the preferred sintering temperature is 1000°C or more and 1350°C or less. A green body is obtained by HIP. This green body is used as a raw material to obtain the above-mentioned precipitation hardened alloy. EXAMPLES
[0053] The effects of the present invention will be clarified by the following examples, but the present invention should not be construed as being limited based on the description of these examples.
[0054] [Example 1] A raw material having a predetermined composition was prepared. The raw material was heated in an alumina crucible in an argon gas atmosphere by high-frequency induction heating. The raw material was melted by this heating to obtain a molten metal. The molten metal was dropped from a nozzle with a diameter of 5 mm located under the crucible. Nitrogen gas was sprayed onto the molten metal to obtain a powder. The powder was classified to adjust the particle size to 500 μm or less. The composition of this powder is shown in Table 1 below. The powder was filled into a capsule made of carbon steel with a diameter of 100 mm and a height of 100 mm. The capsule was vacuum degassed. The capsule was sealed to obtain a billet. The billet was subjected to HIP molding. The HIP temperature was 1200° C. A rod-shaped compact was obtained by HIP. The compact was subjected to solution treatment and aging treatment to obtain a precipitation hardened alloy according to Example 1.
[0055] [Examples 2-28 and Comparative Examples 29-37] Except for changing the composition of the raw materials, the compacts (precipitation hardened alloys) according to Examples 2 to 28 and Comparative Examples 29 to 37 were obtained in the same manner as in Example 1. The compositions of the respective alloys are shown in Tables 1 and 2 below.
[0056] [Corrosion resistance] A test piece was produced by cutting from the molded body (precipitation hardened alloy). The size of this test piece was 10 mm x 10 mm x 15 mm. The mass of this test piece was measured. This test piece was immersed in a 10% aqueous solution of hydrofluoric acid for 10 hours. The temperature of this aqueous solution was 40°C. Furthermore, the mass of the test piece was measured. It was ranked according to the following criteria. A: The mass loss due to immersion is 1.0g / m2 / h or less. B: The mass loss due to immersion is greater than 1.0 g / m2 / h. The results are shown in Tables 1 and 2 below.
[0057] [Hardness] The compact (precipitation hardened alloy) was polished to obtain a test piece with parallel upper and lower surfaces. The Vickers hardness H1 of this test piece was measured and rated according to the following criteria. A: Hardness is 380HV or more. B: Hardness is less than 380HV. The results are shown in Tables 1 and 2 below.
[0058] [Hardness increase] The Vickers hardness H2 of the compact before aging treatment was measured, and the difference from the hardness H1 (H1-H2) was calculated. The samples were rated according to the following criteria. A: The difference (H1-H2) is 50 or more. B: The difference (H1-H2) is less than 50. The results are shown in Tables 1 and 2 below.
[0059] [Transverse rupture strength] A test piece was cut from the compact (precipitation hardened alloy). The size of the test piece was 2 mm x 2 mm x 20 mm. The test piece was subjected to a three-point bending test. The distance between the supports was 10 mm. The test pieces were graded according to the following criteria. A: The flexural strength is 1.5 GPa or more. B: The flexural strength is less than 1.5 GPa. The results are shown in Tables 1 and 2 below.
[0060] [Table 1]
[0061] [Table 2]
[0062] In Tables 1 and 2, the alloy according to Comparative Example 29 has many Mo compounds dispersed in the grain boundaries and matrix, and therefore has poor corrosion resistance, hardness, hardness increase and flexural strength. The alloy according to Comparative Example 30 has a low content of Cr and Mo, and has few Mo compounds dispersed in the grain boundaries and matrix, and therefore has poor corrosion resistance and flexural strength. The alloy according to Comparative Example 31 has many Mo compounds dispersed in the grain boundaries and matrix, and therefore has poor corrosion resistance. The alloy according to Comparative Example 32 does not contain Al, and does not precipitate γ', and therefore has poor hardness and hardness increase. The alloy according to Comparative Example 33 has many Mo compounds dispersed in the grain boundaries and matrix, and therefore has poor corrosion resistance, hardness and hardness increase. The alloy according to Comparative Example 34 has many Mo compounds dispersed in the grain boundaries and matrix, and therefore has poor corrosion resistance, hardness and hardness increase. The alloy according to Comparative Example 35 does not contain Al, Nb, or Ti, and does not precipitate γ' phase or Mo compounds, so it is inferior in hardness, hardness increase, and flexural strength. The alloy according to Comparative Example 36 does not contain Al, and does not precipitate γ' phase, so it is inferior in hardness and hardness increase. The alloy according to Comparative Example 37 does not contain Al, and does not precipitate γ' phase, so it is inferior in hardness and hardness increase. On the other hand, the alloys according to each Example are excellent in various performances. From these evaluation results, the superiority of the present invention is clear. [Industrial Applicability]
[0063] The Ni-Cr-Mo precipitation hardened alloys described above are suitable for various products obtained through plastic working.
Claims
1. Cr: 18.0% by mass or more and 28.0% by mass or less, Mo: 10.0% by mass or more and 25.0% by mass or less, and Al: 1.0% by mass or more and 3.0% by mass or less Contains A Ni-Cr-Mo-based precipitation hardening alloy, the balance of which is Ni and unavoidable impurities, The alloy has a metal structure including grain boundaries, a matrix, and a γ' phase dispersed in the matrix, The matrix contains Ni, Cr and Mo, A precipitation hardening alloy, in which the total P1 of the ratio of Cr and the ratio of Mo in the matrix is 25 mass% or more and 50 mass% or less.
2. the metal structure has a Mo compound phase dispersed in the grain boundaries and the matrix, 2. The precipitation hardened alloy according to claim 1, wherein the sum P2 of the ratio of Cr and the ratio of Mo in the Mo compound phase is 60 mass % or more and 80 mass % or less.
3. a ratio R1 of the sum of the mass of Al in the matrix and the mass of Al in the γ' phase dispersed in the matrix to the total mass of Al is 0.6 or more; 3. The precipitation hardened alloy according to claim 2, wherein a ratio R2 of the mass of Al in the Mo compound phase dispersed in the grain boundaries and matrix to the total mass of Al is 0.4 or less.
4. Cr: 18.0% by mass or more and 28.0% by mass or less, Mo: 10.0% by mass or more and 25.0% by mass or less, and Al: 1.0% by mass or more and 3.0% by mass or less Contains Further containing 2.0 mass% or less of Nb and / or 2.0 mass% or less of Ti, A Ni-Cr-Mo-based precipitation hardening alloy, the balance of which is Ni and unavoidable impurities, The alloy has a metal structure including grain boundaries, a matrix, and a γ' phase dispersed in the matrix, The matrix contains Ni, Cr and Mo, A precipitation hardening alloy, in which the total P1 of the ratio of Cr and the ratio of Mo in the matrix is 25 mass% or more and 50 mass% or less.
5. the metal structure has a Mo compound phase dispersed in the grain boundaries and the matrix, 5. The precipitation hardened alloy according to claim 4, wherein the sum P2 of the ratio of Cr and the ratio of Mo in the Mo compound phase is 60 mass % or more and 80 mass % or less.
6. a ratio R1 of the sum of the mass of Al in the matrix and the mass of Al in the γ' phase dispersed in the matrix to the total mass of Al is 0.6 or more; 6. The precipitation hardened alloy according to claim 5, wherein a ratio R2 of the mass of Al in the Mo compound phase dispersed in the grain boundaries and matrix to the total mass of Al is 0.4 or less.
7. 7. The precipitation hardened alloy according to claim 5, wherein a ratio R3 of the mass of Nb in the Mo compound phase dispersed in the grain boundaries and the matrix to the total mass of Nb is 0.6 or less.
8. 8. The precipitation hardened alloy according to claim 5, wherein a ratio R4 of the mass of Ti in the Mo compound phase dispersed in the grain boundaries and the matrix to the total mass of Ti is 0.6 or less.
Citation Information
Patent Citations
JP1973016950B1
Directionally solidified castings
JP1977068022A
High-strength hi-base super alloy for single-crystal bolt excellent in stress corrosion cracking characteristics
JP1987180029A
Corrosion-resisting ni-base alloy wire rod combining high strength with high hardness
JP1987260033A
Member for fluororesin forming machine
JP1994200343A
